On teaching the concepts of number sequence and its limit in academic lyceums - Aroyev Dilshod Davronovich; Yusupova Aigul Rustamjon qizi (International Journal on Integrated Education, 2023)
This article analyzes the teaching of the concepts of number sequence and its limits in academic lyceums and offers suggestions for its improvement.